1996
DOI: 10.1016/s0005-2736(96)00173-3
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of 2,4-dichlorophenoxyacetic acid (2,4-D) with cell and model membranes

Abstract: 2,4-dichlorophenoxyacetic acid (2,4-D), a widely used herbicide, is a component of the "agent orange' whose toxicity has been extensively studied without definite conclusions. In order to evaluate its perturbing effect upon cell membranes, 2,4-D was made to interact with human erythrocytes and molecular models. These studies were performed by scanning electron microscopy on red cells, fluorescence spectroscopy on dimyristoylphosphatidylcholine (DMPC) large unilamellar vesicles and X-ray diffraction on multilay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…2). Previous investigations performed by Suwalsky et al (1996) as well as by Bukowska and Zatorska (2003) proved that 2,4-D-Na induced changes in erythrocytes morphology. Suwalsky et al (1996) used scanning electron microscopy and revealed that normal red blood cells were converted into echinocytes, probably due to a massive insertion of the 2,4-D-Na into the outer lipid monolayer of the plasma membrane.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…2). Previous investigations performed by Suwalsky et al (1996) as well as by Bukowska and Zatorska (2003) proved that 2,4-D-Na induced changes in erythrocytes morphology. Suwalsky et al (1996) used scanning electron microscopy and revealed that normal red blood cells were converted into echinocytes, probably due to a massive insertion of the 2,4-D-Na into the outer lipid monolayer of the plasma membrane.…”
Section: Discussionmentioning
confidence: 85%
“…The analysis of anisotropy value for ANS showed that the phenoxyherbicides examined at their highest concentration (2 mM) caused an increase in erythrocytes membrane fluidity (Table 1), which was surely connected with their impact on protein-lipid interactions. Suwalsky et al (1996) studied the effect of 2,4-D on dimyristophosphatidylcholine large unilamellar vesicles (DMPC LUV). They observed that 2,4-D was incorporated into DMPC LUV bilayer, deeply penetrated hydrocarbonchains region, and provoked its structural disorder.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Toxic influence of 2,4-D may provoke disturbances in bilayer phospholipid structure that plays an important role in the correct function of cell membrane. Phenoxyherbicides interact with proteins and lipids of erythrocyte membrane (Suwalsky and Berites, 1996). Indeed, Janik and Wolf (1992) have demonstrated the inhibitory effect of chlorinated compounds on the Ca-ATPase which indicates a toxic effect to human erythrocytes functions.…”
Section: In Vitro Studiesmentioning
confidence: 99%